Jerusalem Studies in Jewish Folklore - Alexander-Frizer, Tamar; Hasan-Rokem, Galit; Salamon, Hagar (The Mandel Institute of Jewish Studies, 2019)
Articles:Yona Sabar | Grandpa Ephraim and Grandpa Menashe: Two Opposite Characters, Based on Personal and Communal Childhood Memories Dov Cohen | 'The Holy Island of Chios': New Findings Concerning the Purported Burial Place of R. YaꜤakov ben Asher (BaꜤal Ha-Turim) on the Island of Chios and Pilgrimages to His GravesiteItamar Drori | Rabbi Israele Costa's 'Miḳweh Yisrael' (1851): The Beginning of the Adapted Jewish Story for Youth Carmela Abdar | Reflections on Magical Texts on Jewelry and Amulets of Jewish Women and Children from Yemen and HabbanTom Fogel | JaꜤle - Yemenite Nostalgia in a Jerusalem CaféJacqueline Laznow | 'I Recognized the Holidays According to the Food': Tradition and Memory in the Jewish Community of Argentina Reviews: Eli Yassif | The First Book of Jewish Jokes: The Collection of L. M. Büschenthal, ed. Elliott Oring, Bloomington, IN: Indiana University Press, 2018 Dudu Rotman | Vered Tohar, The Book of Tales, Sermons and Legends. Anthology of Hebrew Stories from the Print Era: An Annotated Edition, Tel Aviv: Hakibbuz Hameuchad 2017, 201 pp